Enemy’s Image Construction. Polarization and Depreciation in the Political Discourse - Lüger, Heinz-Helmut (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
The enemy’s image can be socially constructed on the level of single persons, political parties or whole country. This distortion propaganda targets the enemy’s portrayal to emphatically de-cline the stances and the positions of a given political opponent. Linguistically, the enemy’s image construction can be formed in various ways depending on the emotional engagement of the speaker: These forms varies from just negative evaluations to profound contempt and hate speech. This article examines this phenomenon in some historical documents concerning the outbreak of the World War 1.